2022
DOI: 10.3390/genes13101691
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Phylogenetic Analyses of Complete Chloroplast Genomes of Scrophularia incisa Complex (Scrophulariaceae)

Abstract: The Scrophularia incisa complex is a group of closely related desert and steppe subshrubs that includes S. incisa, S. kiriloviana and S. dentata, which are the only S. sect. Caninae components found in Northwest China. Based on earlier molecular evidence, the species boundaries and phylogenetic relationships within this complex remain poorly resolved. Here, we characterized seven complete chloroplast genomes encompassing the representatives of the three taxa in the complex and one closely related species, S. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Our preliminary analyses of nuclear ribosomal (nr) and chloroplast (cp) DNA placed this species complex as a monophyletic group embedded in sect. Caninae clade ( Wang, 2015 ). Of those, S. incisa Weinm.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary analyses of nuclear ribosomal (nr) and chloroplast (cp) DNA placed this species complex as a monophyletic group embedded in sect. Caninae clade ( Wang, 2015 ). Of those, S. incisa Weinm.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the expansion and contraction of the IR, LSC, and SSC regions are common during evolution and are the main reason for variations in plastome size ( Ravi et al., 2007 ; Downie and Jansen, 2015 ; Daniell et al., 2016 ). Significant contraction of IR region was observed among Linderniaceae species ( Supplementary Figure 2 ), which was also common in Lamiales, such as Gesneriaceae ( Gu et al., 2020 ), Lamiaceae ( Su et al., 2022 ), Oleaceae ( Long et al., 2023 ), Plantaginaceae ( Xie et al., 2023 ), and Scrophulariaceae ( Wang et al., 2022 ). Notably, the IR boundaries did not coincide exactly in the three populations of L. polygonoides , but they had the same plastome size.…”
Section: Discussionmentioning
confidence: 92%
“…However, geographical and ecological factors may continually change these characteristics in species of the genus Veronica 28, 29 . Recent taxonomy studies have utilized cp genomes to assess the genetic relationship between related species [30][31][32][33] . The basic groups of nine species in this genus range in size variations from 149386 to 152319bp, indicating that each of these species has signi cantly different cp gene sizes [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%